Program Kampus Mengajar Angkatan 4 Sebagai Usaha Peningkatan Kemampuan Literasi dan Numerasi SDN Batonaong 1, Arosbaya - Aprilia Eka Pratiwi; Didiek Tranggono (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Campus teaching is a program designed by the Ministry of Higher Education to provide opportunities for students to develop themselves through activities outside the lecture class. Through the teaching campus program, students have activities that are their responsibility in assisting learning activities, assisting with technology adaptation, and assisting with administration at the school where they are assigned. The purpose of this study was to find out how the implementation of campus teaching at SDN Batonaong 1. This research method uses a qualitative descriptive method. Observations, interviews and documentation were used for data collection. The data collected was then processed using qualitative data processing techniques from Miles and Hubermen. SDN Batonaong 1 is an elementary school that is the target of the campus teaching program batch 4 to improve literacy, numeracy and technology adaptation skills. With this program, it is hoped that it can provide benefits for the problems and needs of schools, teachers, and students at SDN Batonaong 1. Apart from that, this activity is also able to become an arena for students to hone their potential to develop education in Indonesia.